1985
DOI: 10.1113/expphysiol.1985.sp002885
|View full text |Cite
|
Sign up to set email alerts
|

MEMBRANE POTENTIAL MEASUREMENTS IN ISLETS OF LANGERHANS FROM ob/ob OBESE MICE SUGGEST AN ALTERATION IN [Ca2+]i‐ACTIVATED K+ PERMEABILITY

Abstract: SUMMARYHigh-resistance micro-electrodes were used to measure membrane potentials in f-cells from islets of Langerhans of ob/ob obese mice (Norwich colony). In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…[44]. Recordings with intracellular electrodes have shown that glucose induces oscillations of the membrane potential with bursts of action potentials in ob/ob beta cells within intact islets, but have identified several differences with the electrical pattern in normal mouse islets [45]. However, the authors emphasised that their observations, made with ob/ob mice from the Aston colony, might not be applicable to ob/ob mice of the Umea colony.…”
Section: Discussionmentioning
confidence: 99%
“…[44]. Recordings with intracellular electrodes have shown that glucose induces oscillations of the membrane potential with bursts of action potentials in ob/ob beta cells within intact islets, but have identified several differences with the electrical pattern in normal mouse islets [45]. However, the authors emphasised that their observations, made with ob/ob mice from the Aston colony, might not be applicable to ob/ob mice of the Umea colony.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, exposure to apamin depolarized the ob/ob @cell membrane as is the case for quinine in islets from normal mouse [2] and, furthermore, the toxin impaired the hyperpolarizing effect of CCCP. This uncoupler of oxidative phosphorylation has been reported to hyperpolarize the P-cell membrane through activation of Px-Ca, leading to cessation of spike activity, both in islets from albino mice [14] and from ob/ob mice [9]. In addition, apamin affected the spike characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…As in other ob/ob P-cells, bursts of variable duration were recorded (see [9]). Addition of 4 nM apamin slightly increased the spike amplitude, whilst exposing the same islet to 40 nM apamin clearly increased the time spent in the active phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations